Electromagnetic interference prediction of power converter including nonlinear behavior of inductive component - Liu, Yitao (2014)
Electromagnetic compatibility (EMC) is one of the important design considerations for power convertor design. Development of electromagnetic interference (EMI) noise model in power convertor design forms a key part for EMI simulation and prediction purposes. With an accurate EMI noise model, the EMI filter can be systematically designed to comply with the relevant EMC standards with good confidence. In addition, the power quality of the power system has become a major concern due to more nonlinear loads connected to the power grid, especially the switching power supplies in most consumable electronics. To reduce power harmonics due to these power converters, passive or active power factor correction (PFC) circuits are part of power converter designs. Active PFC converter can achieve very high power factor but it requires a high frequency active switch, which increases the EMI generated by the convertor. Interleaved PFC converter is a popular topology in PFC converter due to its lower EMI noise and larger output power capacity. The main beneﬁts of the interleaved boost converter when compared with the conventional non-interleaved boost converter are that the inductor volume, the current rating of the semiconductors, and the input current ripple can be reduced. Flyback PFC converter is a simple and yet efficient topology and therefore becomes a popular choice for most applications. In any converter design, inductors and transformers are critical components. To achieve large inductance with smallest possible size, these inductors and transformers are wound on magnetic cores with very high permeability. To simplify the power convertor design process, they are usually considered to be linear with constant inductances. In reality, their inductances depend on the current as well as the frequency due to nonlinearity of the magnetic cores. In this thesis, a comprehensive mathematical model has been developed that takes into account the nonlinear behavior of the magnetic core so that the actual operating condition of the inductor or transformer in the power converter can be emulated. The model allows more realistic conducted EMI prediction of the power convertor, which prevents overdesign of EMI filter for EMC compliance purpose. Using the interleaved boost converter and the flyback converter as design examples, the model that includes the nonlinearity of the inductor or transformer has been validated experimentally.